SILENT CRISIS IN CHILDREN: PERAN KOMUNIKASI KELUARGA DAN POLA ASUH ORANG TUA TERHADAP PEMBENTUKAN KEPERCAYAAN DIRI ANAK USIA SEKOLAH - Sri Rahayu; Dian Apri Nelyanti; Amirul Kadafi; Miftachul Sobirin (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2026)
Self-confidence is a crucial aspect of psychosocial development in school-aged children. Low self-confidence can negatively affect academic achievement, social interactions, and overall mental well-being. The family environment, particularly family communication and parenting styles, plays a significant role in shaping children's self-perception and confidence. However, modern social changes and increasing demands of daily life have reduced the quality of family communication, creating a "silent crisis" that often goes unnoticed and may hinder children's psychosocial development. This study aimed to analyze the role of family communication and parenting styles in the development of self-confidence among school-aged children. This study employed a quantitative analytic design with a cross-sectional approach. A total of 40 respondents participated in the study, consisting of 27 females (67.5%) and 13 males (32.5%), selected using a purposive sampling technique. Data were collected using the Family Communication Scale (FCS), Parenting Style Questionnaire (PSQ), and Self-Confidence Scale for Children. Data analysis included univariate, bivariate (Chi-square test). The findings revealed a significant relationship between family communication and children's self-confidence (p < 0.05). Parenting style was also significantly associated with self-confidence, with democratic (authoritative) parenting showing the strongest positive influence compared to authoritarian and permissive parenting styles (p < 0.05). Furthermore, family communication emerged as the most dominant factor influencing the development of self-confidence among school-aged children. The Conclusion Effective family communication and democratic parenting styles play an important role in fostering self-confidence among school-aged children. Strengthening parent–child communication and promoting positive parenting practices may contribute to improving children's psychosocial development and emotional well-being.